Conserved charged residues at the surface and interface of epithelial sodium channel subunits – roles in cell surface expression and the sodium self‐inhibition response. (17th March 2014) - Edelheit, Oded; Ben‐Shahar, Refael; Dascal, Nathan; Hanukoglu, Aaron; Hanukoglu, Israel
<x xml:space="preserve">Abstract</x> The epithelial sodium channel (ENaC) is composed of three homologous subunits that form a triangular pyramid‐shaped funnel, anchored in the membrane with a stem of six transmembrane domains. We examined the structure–function relationships of 17 conserved charged residues on the surface of the ectodomain of human γ‐ENaC subunit by alanine mutagenesis and co‐expression with α‐ and β‐ENaC subunits in Xenopus oocytes. The results showed that Na+ conductance of cells expressing these mutants can be accounted for by two parameters: (a) the ENaC density on the cell surface as measured by the fluorescence of an α‐EnaC–yellow fluorescent protein hybrid and (b) the sodium self‐inhibition (SSI) response that reflects the open probability of the channel (Po). Overall, the activity of all 17 mutants was correlated with surface levels of ENaC. There was no significant correlation between these parameters measured for α‐ and γ‐ENaC subunit mutants at nine homologous positions. Thus, the functions of most of the homologous surface residues examined differ between the two subunits. Only four mutants (K328, D510, R514 and E518) significantly reduced the SSI response. The α‐ENaC homologs of three of these (R350, E530 and E538) also severely affected the SSI response. The cASIC1 homologs of these (K247, E417, Q421) are located at the interface between subunits, on or about the ion pathway at the rotational symmetry axis in the center of the trimer. Thus, it is likely that these residues are involved in conformational changes that lead to channel constriction and the SSI response upon Na+ ion flooding.